1994
DOI: 10.1164/ajrccm.149.6.8004317
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosing alveolitis associated with systemic sclerosis has a better prognosis than lone cryptogenic fibrosing alveolitis.

Abstract: Fibrosing alveolitis associated with systemic sclerosis (FASSc) is considered to be histologically and radiologically indistinguishable from lone cryptogenic fibrosing alveolitis (CFA). To date, the natural history of the two diseases has not been compared directly in large groups of patients followed at a single institution. We evaluated the survival of 205 patients with CFA and 68 patients with FASSc. Deaths during the follow-up period were reported in 142 patients with CFA (70%) and in 11 patients with FASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0
11

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(157 citation statements)
references
References 36 publications
9
136
0
11
Order By: Relevance
“…Finally, we tested for association using a more stringent phenotype defi nition, the most com mon form of IIP. 5 These observations raise questions regarding shared and distinct etiologic and pathologic events underlying the development of lung fi brosis in its idiopathic and SSc-associated forms.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we tested for association using a more stringent phenotype defi nition, the most com mon form of IIP. 5 These observations raise questions regarding shared and distinct etiologic and pathologic events underlying the development of lung fi brosis in its idiopathic and SSc-associated forms.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the identification and staging of pulmonary involvement is very important for the management of the disease. For many years, IPF and FASSc were considered to be histologically similar conditions, despite the better prognosis in FASSc [61]. Recent studies in SSc demonstrated that NSIP is the most common histological pattern, followed by UIP in SSc [62][63][64].…”
Section: Systemic Sclerosis (Scleroderma)mentioning
confidence: 99%
“…The authors of this present study have published previous articles demonstrating better prognosis in patients with interstitial lung disease secondary to SSc than those with idiopathic pulmonary fibrosis (16,17). More recently, they compared BAL cellularity between the 2 groups and found that patients with cryptogenic or idiopathic fibrosing alveolitis had higher levels of both neutrophils and eosinophils in the BAL fluid, but the eosinophil levels were ultimately found to be linked to more extensive lung disease (18).…”
Section: Histopathologic Subsets Of Fibrosing Alveolitis Inmentioning
confidence: 68%